Investigating the Impact of Implementing an Independent Curriculum on Problem-Solving Skills in Chemical Engineering Education - Adrian Calvari (International Journal of Curriculum Development, Teaching and Learning Innovation, 2024)
This research investigates the impact of implementing an independent curriculum on student problem-solving skills within the chemical engineering department. The study employs a quasi-experimental design, comparing pre- and post-test scores of students exposed to the traditional curriculum with those of students experiencing the independent curriculum intervention. Quantitative analysis reveals a significant improvement in problem-solving skills among students in the independent curriculum group, as indicated by higher post-test scores compared to their peers in the traditional curriculum group. Qualitative data further support these findings, highlighting the empowering effect of the independent curriculum on student learning experiences and attitudes towards education. However, unexpected challenges and unintended consequences associated with the implementation of the independent curriculum are also identified, underscoring the need for ongoing reflection, adaptation, and support mechanisms. The findings of this research have important implications for curriculum design, pedagogical practice, faculty development, and institutional policy in chemical engineering education, providing insights into effective strategies for fostering critical thinking, creativity, and practical problem-solving skills among students.